Unfulfilled need: reasons for insufficient ICT skills In South Africa - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2018)
The ubiquity of information and communication technologies (ICT) in all aspects of life has an important consequence in today's world: shortage of skilled personnel in this area. Although the dotcom bubble in 2000 had an adverse effect in the requirement for ICT skills in industrialized countries, this is not applicable for many developing countries, where ICT skills are in high demand. Even though South Africa is one of these countries, ICT enrolments and graduations do not meet ICT skills demand. An important reason for the skills gap in this area is the negative perceptions of university students about ICT. It was found that there were substantial differences in the perceptions of ICT and non-ICT students about the ICT profession. Some of the differences are subjective, such as perceiving the ICT profession as boring, while some other are ungrounded, such as that ICT jobs are less secure and the unemployment rate is high. The findings may be pertinent not only for South Africa, but also other developing countries where negative perceptions about ICT hinder prospective students to enrol to computer-related programs.
Keywords: ICT education; ICT skills gap; ICT enrolment; ICT students; South Africa; CHOICE; CAREER